2022
DOI: 10.3390/ijerph19063710
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Addiction Prevalence and Its Association on Academic Performance, Physical Health, and Mental Well-Being among University Students in Umm Al-Qura University (UQU), Saudi Arabia

Abstract: Smartphone use can lead to smartphone addiction, which is a growing concern worldwide. However, there are limited studies about smartphone addiction and its impacts on university students in Saudi Arabia. This study aims to fill this gap. This is a quantitative study conducted among undergraduate students in Umm Al-Qura University (UQU), Saudi Arabia from May 2019 and February 2021. Study data were collected using both online and hard copy administered surveys. A self-administered questionnaire, Grade point av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 99 publications
(119 reference statements)
9
44
2
Order By: Relevance
“…As such, these students may be more susceptible to some of the negative psychological consequences associated with problematic smartphone use, such as anxiety [19,42], depression [9,36,42], and loneliness [14,36]. Importantly, this group contained 22% of the sample, which is in contrast to other recent studies which have found prevalence rates of 52-68% for problematic smartphone use among university students (e.g., [65][66][67]). This discrepancy in findings emphasizes the importance of person-centered work which allows for a more nuanced investigation of the heterogeneity of symptom/feature cooccurrence and thus avoids overpathologizing behaviours which have become largely normative.…”
Section: Discussionmentioning
confidence: 77%
“…As such, these students may be more susceptible to some of the negative psychological consequences associated with problematic smartphone use, such as anxiety [19,42], depression [9,36,42], and loneliness [14,36]. Importantly, this group contained 22% of the sample, which is in contrast to other recent studies which have found prevalence rates of 52-68% for problematic smartphone use among university students (e.g., [65][66][67]). This discrepancy in findings emphasizes the importance of person-centered work which allows for a more nuanced investigation of the heterogeneity of symptom/feature cooccurrence and thus avoids overpathologizing behaviours which have become largely normative.…”
Section: Discussionmentioning
confidence: 77%
“…Alsiwed et al [3] found that 58.2% of medical students used smartphones for more than five h per day. Another study from Saudi Arabia found that 67.0% of respondents were smartphone-addicted, with average use of 6-11 h per day [19]. Damasceno et al [41] found that Brazilian young people spent more than four h per day on smartphones.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant relationship between the number of hours using the smartphone and the prevalence of addiction. The more hours of looking at electronic devices, the more likely to become addicted [18][19][20][21][22]. Previous studies argued that the younger users of electronic devices are more likely to develop musculoskeletal symptoms because of the early launching of technology in their daily lives [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…For young college students, due to quasi-permanent access to the internet, smartphones are often used to fill in almost any gaps in their life ( Harrison and Gilmore, 2012 ). Although smartphone use is accompanied by advantages such as sociability, entertainment, and information finding, it may also lead to adverse effects on physical and mental health due to dependence or addiction to mobile phones ( Kayis et al, 2021 ; Alotaibi et al, 2022 ; Kwon et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%